Characteristics of feeding and breeding practices for intensification of smallholder dairy systems in the Kenya highlands - Bebe, B.O.; Udo, H.M.J.; Thorpe, W.R. (2008)
This study aimed at better understanding of the characteristics of feeding and breeding practices smallholder farmers adopt in intensifying their dairy production. Use of hired labour for fodder gathering, growing of fodder crops and purchase of feeds increased with increasing intensification, but Bos taurus breeds did not respond to increasing feeding intensification while Bos indicus cattle responded, calving at earlier age and yielding more milk. Overall, first calving occurred at 32 months, but days open prolonged to 250 days with milk yield of 4 litres per day of calving interval. A principal component analysis extracted six feeding and breeding components, explaining 71.79% of the total variations in feeding and breeding practices for dairy intensification. The six components were labelled: non-intensified feeding and breeding; breeding decisions based-intensification; high external resource based-intensification; moderate resource based-intensification; resource poor based-intensification; and moderate external resource based-intensification. These characteristics points to some 'evolutionary process' of intensification involving feeding and breeding decisions, depending on the risk-bearing capacity of the household. Intensification enhancing interventions for smallholders need be considered in the context of the household economy. Interventions on feeding and breeding have to be packaged together holistically if intensification is to enhance productivity. A selective intervention on only one of these is associated with low productivity levels, only contributing to sustaining family subsistence livelihoods.